ANALISIS TINGKAT AKURASI SIGNAL INDIKATOR EXPONENTIAL MOVING AVERAGE PADA BITCOIN (PERIODE 2017 – 2023) - Rizwan Nurfalah; Habi Baturohmah; Rieska Rahayu Ayuningsih (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
In the current era, technology is growing rapidly in various sectors, one of which is quite significant, namely the presence of digital currency with blockchain technology which brings changes in economic movements by carrying the name cryptocurrency. In this study the aim is to measure data on the accuracy of the Exponential Moving Average indicator in technical analysis of digital currency cryptocurrency. This research takes Bitcoin digital currency data for the period 2017 – 2023 as the object of the research conducted. The results of research on the level of accuracy of the Exponential Moving Average indicator on Bitcoin during the period 2017 – 2023 is to obtain an accuracy rate of 53.33% by knowing the level of accuracy in making decisions to make sales and purchases so as an investor can minimize risk in investing.